Effects of hydrocolloids as texture improver in coriander bread - Das, Lipi (J Food Sci Technol, 2014)
An attempt was made to study the effects of hydrocolloids on loaf weight, volume, crumb grain characteristics, crumb moisture, firmness and dough rheological properties on 3.0 % coriander leaf supplemented breads. Carrageenan (CA), carboxymethylcellulose (CMC), guar gum (GG) and xanthan gum (XG) were added in the proportions of 0.25, 0.5, 0.75 and 1.0 % w/w of 100 g wheat flour. Addition of hydrocolloid increased the loaf volume and decreased the average cell area. An inverse relationship was observed between specific volume and average cell area. XG showed uniform change in crumb moisture on storage at all levels of substitution. However highest loss of moisture occurred in bread samples supplemented with GG. Crumb firming kinetics using Avrami’s model showed slower firming rates for GG and CMC. High complex modulus (G*) values were observed in breads with 0.75 and 1.0 % XG.